Situation Report: Bulgaria, 7 December 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Plan for 1985: Again New Procedures / by Rada Nikolaev Politburo Decision on Sofia University / by Rada Nikolaev More Gold for the Bulgarian Girl Gymnasts